Effects of Polyoxymethylene Dimethyl Ethers Addition in Diesel on Real Driving Emission and Fuel Consumption Characteristics of a CHINA VI Heavy-Duty Vehicle - Haoming Gu; Shenghua Liu; Yanju Wei; Xibin Liu; Xiaodong Zhu; Zheyang Li (Energies, 2022)
Polyoxymethylene dimethyl ethers (PODE), as the most potential oxygenated alternative fuel for diesel engines, is widely investigated. Considering the importance of research on real driving emissions (RDE) and the few studies focus on the emission characteristics of the PODE/diesel blended fuels under real driving conditions, a portable emission measurement system (PEMS) was applied to measure the RDE of a heavy-duty tractor fueled with diesel or PODE/diesel blends. The tests were carried out in accordance with the relevant regulations of the CHINA VI emission standards. The second-by-second data from PEMS and the OBD system were utilized to construct engine transient operating maps. The results indicated that the addition of PODE can still decrease CO and PN emissions significantly under real driving conditions, although the low load conditions are still the areas of high brake specific CO and brake specific PN emissions. The NOx emissions, however, were not reduced as the results of the steady-state experiment of the same model of the engine. Fuel mass consumption raised when PODE was added, while the overall brake thermal efficiency improved, especially for the blending ratio of 30%, up to 40.3%, which is higher than 38.4% of pure diesel operation.